2020
DOI: 10.1111/ajco.13403
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of interleukin‐35 as a potential prognostic factor for gastric cancer

Abstract: Aims Interleukin‐35 (IL‐35), a novel anti‐inflammatory cytokine, has recently been implicated in tumor development, progression, and survival. However, the relationship between serum IL‐35 levels and gastric cancer (GC) is inconclusive. Here, we performed this study to clarify the role of serum level of IL‐35 in GC patients. Methods We enrolled 180 GC patients and 170 healthy controls and used enzyme‐linked immunosorbent assay to detect serum IL‐35 levels. The clinical relevance between IL‐35 and clinical path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Fan et al 128 revealed IL-35 is involved in the proliferation of gastric cancer cells by upregulating the expression of Ki67 and reducing apoptosis. Similarly, Gu et al 129 observed that the enhanced serum level of IL-35 correlates with disease prognosis in gastric cancer patients. Furthermore, Chen et al demonstrated the elevated level of IL-35 in serum and tumor tissues of breast cancer patients is associated with tumor progression.…”
Section: Immune-suppressive Cytokines Il-10 Tgf-β Il-4 and Il-35 In Cancer And Immunotherapymentioning
confidence: 84%
“…Fan et al 128 revealed IL-35 is involved in the proliferation of gastric cancer cells by upregulating the expression of Ki67 and reducing apoptosis. Similarly, Gu et al 129 observed that the enhanced serum level of IL-35 correlates with disease prognosis in gastric cancer patients. Furthermore, Chen et al demonstrated the elevated level of IL-35 in serum and tumor tissues of breast cancer patients is associated with tumor progression.…”
Section: Immune-suppressive Cytokines Il-10 Tgf-β Il-4 and Il-35 In Cancer And Immunotherapymentioning
confidence: 84%
“…Moreover, in patients with arterial hypertension, alterations in IL-12, IL-23, IL-27, IL-35, and IL-37 concentrations are connected with the development of carotid atherosclerotic plaque [157,158]. All aforementioned cytokines are also associated with H. pylori infection [159][160][161][162].…”
Section: H Pylori-related Mets Parameters and Arterial Hypertensionmentioning
confidence: 99%
“…The assessment of the levels of interleukins in the human body can be used as a diagnostic indicator of the development or progression of many diseases (cancers [ 16 , 17 , 18 , 19 ], heart disease [ 20 , 21 , 22 ] and neurological disorders [ 23 , 24 , 25 ]) affecting contemporary society, including kidney diseases [ 26 , 27 , 28 , 29 , 30 ]. That is why it is extremely important to conduct further extensive scientific and clinical research to assess the biological functions of interleukins and their interactions with other cells of the body, which may lead to health deterioration.…”
Section: Introductionmentioning
confidence: 99%